A Increasing learning outcomes for citizenship education courses based on google applications at PGSD FIP UMJ in 2022 - Santoso, Gunawan; Abdulkarim, Aim; Maftuh, Bunyamin; Sapriya, Sapriya; Murod, Ma'mun Murod; Retnasari, Lisa Retnasari (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2023)
A good citizen is, of course, greatly influenced by the national ideology of each country. Citizenship Education (CE), whose mission is to make citizens who are smart, good, and democratic citizens through nationalistic, patriotic, professional, and scientific behavior, This study aims to determine the contribution of pedagogic competence and professional competence to learning outcomes. This study uses a classroom action research (PTK) approach. The research population was PGSD FIP UMJ students. Research data were collected using a questionnaire, and the results were analyzed using regression analysis. The results showed that: (1) there is a significant relationship between pedagogic competence and learning outcomes in the effective category; (2) there is a significant and positive relationship between professional competence and learning outcomes. (3) There is a significant and positive relationship between the effectiveness of pedagogical competence and professionalism simultaneously on student civic learning outcomes. The results have provided valuable experience about the benefits of Google technology-based applications such as Meet, Google form, Classroom, Breakout Rooms, Jamboard, recording, Drive, Docs, Gmail, and whiteboarding for students of the PGSD FIP Study Program, University of Muhammadiyah Jakarta in 2022, according to 88% of the students. For obstacles in the jamboard application, the best resolution that is effective and efficient according to existing conditions is to provide repeated socialization, training, and evaluation monitoring to several students who have no experience in sophistication Google application-based Meet, Google form, Classroom, Breakout Rooms, Jamboard, recording, Drive, Docs, Gmail, and whiteboarding.